PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN DEWAN KOMISARIS, DIREKSI, KOMITE AUDIT TERHADAP PROFITABILITAS PADA PERUSAHAAN KELOMPOK BANK MODAL INTI 1-4 DI INDONESIA - Haditiya Haditiya; Devi Astriani; Ade Trisyanto (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
The purpose of this study is to analyze the effect of CSR, Board of Commissioners, Board of Directors and Audit Committee on the profitability of banking companies in Indonesia which are classified as core capital 1-4 bank groups during the 2021-2023 period. Quantitative methodology is used through multiple linear regression analysis by testing through the relationship between variables. The results showed that CSR, Board of Commissioners, and Audit Committee did not have a significant influence on ROA, indicating a suboptimal role in supporting profitability. In contrast, the Board of Directors showed a significant positive effect on ROA, signaling the importance of their role in strategic decision-making and the implementation of Good Corporate Governance (GCG). This study concludes that the effectiveness of CSR and corporate governance requires improvement to have a more tangible impact on corporate financial performance. The implications of these results emphasize the need for a more integrated CSR strategy and improved quality of supervision by the Board of Commissioners and Audit Committee.